2020
DOI: 10.1016/j.fuel.2020.118569
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stage model for the release of potassium in single particle biomass combustion

Abstract: The release of potassium during biomass combustion leads to several problems as the emissions of particle matter or formation of deposits. K release is mainly described in literature in a qualitative way and this work aims to develop a simplified model to quantitatively describe it at different stages. The proposed model has 4 reactions and 5 solid species, describing K release in 3 steps; during pyrolysis, KCl evaporation and carbonate dissociation. This release model is coupled into a single particle model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Moreover, the char material of the CC sample with additives has an almost 2.5-3-fold content of K atoms. This gives a reason to presume that the used additives initiate the processes of migration of K atoms [32,33] in biomass samples during pyrolysis. It cannot be excluded that besides the K atoms, other atoms may undergo migration with volatiles.…”
Section: The Investigation Of Chars Of Ph CC and Si Samples And Their...mentioning
confidence: 99%
“…Moreover, the char material of the CC sample with additives has an almost 2.5-3-fold content of K atoms. This gives a reason to presume that the used additives initiate the processes of migration of K atoms [32,33] in biomass samples during pyrolysis. It cannot be excluded that besides the K atoms, other atoms may undergo migration with volatiles.…”
Section: The Investigation Of Chars Of Ph CC and Si Samples And Their...mentioning
confidence: 99%
“…Currently, a large number of studies have shown that chlorine enters the gas phase mainly in the form of HCl and KCl during the combustion of biomass. At 700–900 °C, chlorine basically enters 100% into the gas phase, while potassium partially enters the gas phase. All of the potassium volatilized from the biomass existed in the form of KCl in the gas phase, while the remaining chlorine entered the gas phase in the form of HCl within the operating temperature range of the BCFB. The proportion of solid potassium transformed into gaseous potassium in the biomass fuel used in the CBFB was 5% (700 °C), 10% (800 °C), and 30% (900 °C), respectively.…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…Globally, as a renewable energy resource, biomass is seen as a CO 2 neutral fuel due to the carbon cycle and because bioenergy is renewable in nature. , However, biomass energy use accounts for only 14% of the total energy consumption. , Biomass combustion is a convenient way for CO 2 reduction, due to its CO 2 -neutral characteristics, and the relative ease of utilizing as a fuel in the existing pulverized fossil fuel-fired thermal power plants. , …”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, biomass energy use accounts for only 14% of the total energy consumption. 3,4 Biomass combustion is a convenient way for CO 2 reduction, 5 due to its CO 2 -neutral characteristics, and the relative ease of utilizing as a fuel in the existing pulverized fossil fuel-fired thermal power plants. 6,7 Solid biofuels have lower ignition temperatures, lower energy content, and shorter burnout times 8 compared to coal.…”
Section: Introductionmentioning
confidence: 99%